Biochemical parameters as a tool to assess the nutritional status of patients with amyotrophic lateral sclerosis - Monov, Dimitar; Molodozhnikova, Natalia (Frontiers in Neurology, 2024)
Background: The research aims to analyze blood biochemical parameters in patients with amyotrophic lateral sclerosis and to determine whether they can be used to assess their nutritional status.The study included 45 patients diagnosed with amyotrophic lateral sclerosis (ALS): 28 (62.2%) were men and 17 (37.8%) were women. The mean age of study participants was 50.69±7.24 years. The control group consisted of 30 practically healthy individuals.Compared with practically healthy individuals, Patients with ALS had significantly lower blood parameters, including total lymphocyte count (1.49±0.11 vs 2.86±0.25, p <0.05), total protein (60.55±2.38 vs 77.80±4.41, p <0.05), albumin (33.70±2.03 vs 46.49±3.22, p <0.05), urea (3.09±0.36 vs 5.37±0.50, p <0.05), creatinine (51.28±4.42 vs 70.91±5.13, p <0.05) and transferrin (1.84±0.12 vs 2.32±0.10, p <0.05). These parameters correspond to first-degree malnutrition. There were direct correlations between anthropometric and biochemical parameters in the ALS group. BMI correlated with the blood levels of total protein (r=0.22, p<0.05), albumin (r=0.27, p<0.05), urea (r =0.33, p<0.05), creatinine (r=0.30, p<0.05), transferrin (r=0.18, p<0.05), and total lymphocyte count (r=0.20, p <0.05). PNI correlated with the blood levels of total protein (r=0.53, p<0.05), albumin (r=0.87, p<0.05), total cholesterol (r=0.34, p<0.05), transferrin (r=0.40, p<0.05), total lymphocyte count (r=0. 79, p<0.05), urea (r=0, 37, p<0.05), and creatinine (r=0.32, p<0.05).The study presents compelling evidence supporting the utilization of biochemical parameters, including total protein, albumin, urea, creatinine, transferrin, and total lymphocyte count, for potentially evaluating the nutritional status of individuals diagnosed with ALS.